A decade of insecurity paradox in contemporary China, 2008–2017. Issue 2 (15th March 2023) - Ge, Ting; He, Guangye
Abstract: As a primary component of human development program, sense of insecurity (SI) is widely voiced yet unstudied, particularly in developing countries that have gone through a rapid transition, such as China. To map the trend of SI in China, we identify two types, sense of personal insecurity (SPI) and sense of social insecurity (SSI), that have shown opposite trends from 2008 to 2017. While SPI has been declining, SSI seems to grow. To address the extent to which SPI and SSI in China are changing due to age, period, or cohort effects, we adopted a hierarchical age-period-cohort model. The results reveal that period effects are central in defining the trend of SPI and SSI in both rural and urban areas. The changing pattern is largely due to the varying effects of gender, schooling and wealth, three main dimensions of social stratification. Specifically, schooling is more prominent in defining the insecurity pattern in rural areas, while the effects of schooling and wealth are more evident in urban areas.